Spatial agglomeration and business groups: new evidence from Italian industrial districts - Giulio Cainelli; Donato Iacobucci; Enrica Morganti (European Regional Science Association (ERSA), 2004)
This paper is a first attempt to analyse the relationship between spatial agglomeration and firms' organizational structures. It takes advantage of a large data set on Italian business groups that allowed us to analyse the differences in the presence and characteristics of business groups between districts and non district areas. Overall the result confirms the hypothesis that spatial agglomeration of business activities influences firms' organization. Groups are more widespread in industrial districts than in non-district areas; moreover groups in industrial districts are less diversified and more spatially concentrated than groups outside industrial districts. Key words: business groups, industrial districts, spatial agglomeration, firm's organizational forms JEL Classification: L22, R12
Keywords: L22; R12; 330; business groups; industrial districts; spatial agglomeration; firm's organizational forms